Finding Fresh Florida Produce - Jennifer Hillan; Claudia Peñuela (EDIS)
Revised! FCS8708, a 2-page fact sheet by Jennifer Hillan and Claudia Peñuela, provides a chart showing peak times to buy fresh Florida fruits and vegetables. Includes reference. Published by the UF Department of Family Youth and Community Sciences, October 2010.